اللغة الهجين واللغة المولدة - Kirom, Makhi Ulil (Lugawiyyat, 2021)
Language is speech, as Ibn Jinni defined it. This definition goes to the growth of the spoken language in society. It is well known that the spoken language is more developed and used than the written language. This research aims to explain the conditions of the spoken language and its changes. First of all, we divide this spoken language into two parts, pidgin language and creole language. While a pidgin language arises from efforts to communicate between speakers of different languages, a creole language is born from the natural language that develops from the simplifying and mixing of different languages into a new one. This phenomenon is found in many languages, including Arabic. The pidgin language in Arabic is spoken by workers from outside the Kingdom of Saudi Arabia from India, Bangladesh, Pakistan, the Philippines and other countries. They try to converse among themselves in Arabic according to their ability and understanding, this is where the pidgin language originates. And there are many languages was established among peoples for a long time, and the frequent circulation of it among them made it natural to them, so this language became a creole language.